Comparative Analysis of Adhesive Behavior of Rapid-Setting and Slow-Setting Asphalt Emulsions in Tack Coats Evaluated by LCB Test - Burbano, Jorge Luis Argoty (Journal of Posthumanism, 2024)
Interlayer bonding in asphalt pavements is a key factor governing the durability, structural performance, and mechanical response of flexible pavements under traffic loading. Inadequate monolithic action between bituminous layers leads to premature distresses such as slippage, delamination, and fatigue cracking, severely compromising pavement service life. This study presents a comprehensive comparative analysis of the bonding performance of cationic asphalt emulsions of rapid setting (CRR-60 and CRR-65) and slow setting (conventional CRL-1 and polymer-modified CRL-1hm), used as tack coats between dense-graded hot-mix asphalt layers (MDC-19) representative of Colombian specifications. The experimental program was based on the Laboratorio de Caminos de Barcelona (LCB) shear test, standardized in the Spanish specification NLT-382/08, which quantifies the interface shear strength developed at the bonding surface between asphalt layers joined by a tack coat. Five residual binder application rates were evaluated for slow-setting emulsions and four for rapid-setting emulsions (100, 200, 300, 400, and 500 g/m²), with the aim of identifying the optimal dosages that maximize interface strength. In addition, the influence of binder viscosity and the effect of surface dust contamination on bonding performance were assessed. Experimental results revealed marked differences between emulsions as a function of their setting rate. The polymer-modified slow-setting emulsion (CRL-1hm) achieved the highest interface shear strength (0.60 MPa) at a substantially lower optimum application rate (220 g/m²), satisfying European requirements for layers beneath wearing courses. By contrast, rapid-setting emulsions (CRR-60 and CRR-65) required higher application rates (440–445 g/m²) to reach maximum strengths of 0.345 and 0.418 MPa, respectively, values that lie outside the range prescribed by current Colombian specifications (200–300 g/m². Viscosity, governed by residual asphalt content, had a positive effect on bonding, with strength increases of 16–21% between emulsions with different residual contents. Surface dust contamination significantly reduced shear strength, with decreases of 56% for CRR-60 and 29% for CRR-65 at a contamination level of 123.46 g/m², highlighting the critical importance of proper surface cleaning prior to tack coat application. These findings provide essential technical criteria for the selection and dosage of asphalt emulsions for tack coats, with clear implications for improving pavement durability and in-service performance.